POLA KOMUNIKASI ANTAR PEMAIN MOBILE LEGENDS : BANG BANG USIA DEWASA MUDA DI KOTA MADIUN - Nayottama, Fuad Fajar Nayottama; Widiantari, Maria M; Sejati, Veny Ari (Innovative: Journal Of Social Science Research, 2025)
Mobile Legends: Bang Bang (MLBB) has become a popular phenomenon among Generation Z in Madiun City, serving not only as entertainment but also as a medium for building social relationships. Communication among MLBB players tends to be cooperative and supportive, although it can also be aggressive at times. This study aims to explore the patterns of verbal and nonverbal communication among young adult MLBB players in Madiun. The research uses a descriptive qualitative method, based on DeVito’s interpersonal communication theory and Walther’s Computer-Mediated Communication (CMC) theory. The results show that verbal communication patterns are dynamic and creative, utilizing in-game chat, voice chat, and special slang terms such as "gas," "gg," "santuy," and "otw" to coordinate strategies, motivate teammates, and build closeness. The communication styles identified include cooperative, aggressive, and supportive approaches. Meanwhile, nonverbal communication appears through the use of emojis, quick chat, recall spam, and hero gestures, which reinforce verbal messages, express emotions, and enhance team cohesion. These communication patterns help create an enjoyable gaming atmosphere, strengthen teamwork, and foster social interaction among young adult players in Madiun City.